Perancangan Aplikasi Sistem E-Library Pada Smas Andika Menggunakan Bahasa Pemograman Php Dan Mysql - Syatriadi; Putra; Hidayat (Riset Sinergi Indonesia (RISINDO), 2023)
The design of the E-Library at SMAS ANDIKA is to make it easier for students to carry out the process of borrowing books and printing their own proof of book borrowing cards, as well as students being able to download the lesson syllabus individually. In this case, students no longer need to carry a library membership card because every student who first carries out the process of borrowing books will be recorded by the library staff regarding the student's personal data to be entered and stored in the system database so that it can provide relief for the library staff. because every time there is a loan transaction by the same student, the admin no longer needs to input the student's data a second time. Another convenience for admins is managing book borrowing reports, this system automatically records all book borrowing transactions, whether books are being borrowed or books are being returned based on day, month and year.